Connection resilience to nodes failures in ad hoc networks - Trajanov, Dimitar; Filiposka, Sonja; Makraduli, Jani; Grnarov, Aksenti (IEEE, 2004)
The failure of nodes in an ad hoc network not only alters the network topology but also introduces severe changes in the ad hoc network performances. Based on the ad hoc network connection availability model, in this paper we propose measures of ad hoc network fault tolerance expressed as connection resilience to nodes failures and relative connection resilience to nodes failures. Also qualitative evaluation of these measures is presented and then used to evaluate the effects of real measurable ad hoc networks parameters that concern the resilience to nodes failures like number of participants in the ad hoc network, source destination distance, mobility model, average node speed, transmission range, routing protocol and size of the area wherein the nodes are scattered.